2021
DOI: 10.1186/s13287-021-02228-6
|View full text |Cite
|
Sign up to set email alerts
|

Osthole enhances the bone mass of senile osteoporosis and stimulates the expression of osteoprotegerin by activating β-catenin signaling

Abstract: Introduction Osthole has a potential therapeutic application for anti-osteoporosis. The present study verified whether osthole downregulates osteoclastogenesis via targeting OPG. Methods In vivo, 12-month-old male mice were utilized to evaluate the effect of osthole on bone mass. In vitro, bone marrow stem cells (BMSCs) were isolated and extracted from 3-month-old OPG−/− mice and the littermates of OPG+/+ mice. Calvaria osteoblasts were extracted f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Similar results were reported by Li et al; that is, osthole inhibited osteoclast formation and partially reversed bone loss induced by 5/6 nephrectomy in mice through the upregulation of osteoprotegerin (OPG)/RANKL [103]. It was also found that osthole could stimulate the expression of OPG via the activation of β-catenin signaling pathway and enhance the bone mass of senile osteoporosis [104]. Zhang et al discovered that osthole-mediated osteogenesis was related to the activation of the cAMP/CREB signaling pathway and downstream transcription factor osterix expression [105].…”
Section: Osteogenic Activitysupporting
confidence: 85%
“…Similar results were reported by Li et al; that is, osthole inhibited osteoclast formation and partially reversed bone loss induced by 5/6 nephrectomy in mice through the upregulation of osteoprotegerin (OPG)/RANKL [103]. It was also found that osthole could stimulate the expression of OPG via the activation of β-catenin signaling pathway and enhance the bone mass of senile osteoporosis [104]. Zhang et al discovered that osthole-mediated osteogenesis was related to the activation of the cAMP/CREB signaling pathway and downstream transcription factor osterix expression [105].…”
Section: Osteogenic Activitysupporting
confidence: 85%
“…Functionally, BMP2 has a close relationship with binding to N‐propeptide, ( 39 ) and OPG may inhibit osteoclastogenesis. ( 41,42 ) Collectively, our findings suggest that c.187T>A plays a dominant role in OI genesis, and c.175C>T may interact with this dominant site to affect bone formation.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, previous studies have shown that osthole attenuates osteoclast formation by stimulating the activation of β‐catenin‐Osteoprotegerin (OPG) signalling and could be a potential drug for senile osteoporosis. 30 Furthermore, other signalling pathways have been reported to promote fracture healing in osteoporotic bone, such as epidermal growth factor receptor, 31 growth differentiation factor 11‐fat mass, and obesity‐associated protein axis. 32 Besides, oxidative stress and inflammation 33 might promote fracture healing, which requires in‐depth exploration.…”
Section: Discussionmentioning
confidence: 99%